The geology of the Tracy Canyon area, Saguache County, Colorado - Newman, James W., author; Thompson, Tommy B., advisor; Burns, Lary K., committee member; Warren, C. G., committee member; McCallum, M. E., committee member (Colorado State University. Libraries, 1976)
The study area encompasses approximately 30 square kilometers in the Laughlin Gulch and Saguache, Colorado Quadrangles about 13 kilometers southwest of the town of Saguache. Conejos Formation volcanics of the "early intermediate assemblage" as described by Lipman et al. (1970), are mapped as four separate flow units. Pyroclastic rocks, representatives of the second major episode of San Juan volcanism, are absent in the study area. The Conejos Formation volcanics are partially capped by olivine basaltic andesites of the Hinsdale Formation, and represent the "late bimodal eruptive episode." Intrusives in the area represent all of the major volcanic episodes of the northeastern San Juan Mountains. Flows in the study area are commonly tilted gently to the northeast in response to regional deformation associated with development of the Rio Grande block fault system. Faults are expressed as valleys and topographic breaks. They tend to be short or gently curved and follow northeast and northwest trends. Vertical, or steeply dipping faults, commonly bound small horst and graben structures. Many of the faults have histories of recurrent movement, with the latest activity associated with regional crustal extension and development of the Rio Grande Rift. A major northeast-trending lineament, intersecting the Beidell volcanic center, 13 kilometers to the southwest, and the Klondike mining district, 16 kilometers to the northeast, is expressed in the study area by two flow-banded rhyolitic dikes. Hydrothermal alteration extends over an area of approximately 13 square kilometers, centered about an area of small horst and graben structures. A high-silica alteration zone, comprised principally of jasperoid breccias, represents the most intense hydrothermal alteration in the study area. These rocks are irregularly enveloped by an "advanced argillic alteration zone" as defined by Hemley and Jones (1964). Non-brecciated, silicified quartz latites define a third alteration zone. Hydrolytic decomposition of silicate rocks has been interpreted as the most significant hydrothermal alteration process. Hydrothermal alteration and trace metal geochemistry is not consistent with the porphyry ore deposit model (Lowell and Gilbert, 1970), and it is unlikely that a subsurface orebody of this type exists. Therefore, the most likely target for further exploration in the Tracy Canyon area are the jasperoid breccia pipes.
Covers not scanned.
Keywords: Geology -- Colorado -- Saguache County; Geology; Colorado -- Saguache County